Suomen alueella tapahtuneen mannerjäätikön vetäytymisen visualisoiminen - Jussila, Anssi (Helsingfors universitet, 2017)
Studies of the last ice age have been made in Finland since the early 20th century. The result is a wealth of information on activities related to the continental ice sheet and the location of the ice margins. The purpose of this thesis was to find out the usefulness of animations when visualizing research results. Animations have the advantage of sharing a large amount of information in a short time and they often are easier to comprehend compared to texts and images. In addition to this the aim was to visualize dynamics of the ice sheet and its ice margin positions. The materials from different studies that were used in visualization contain visual materials from ice sheet in northern Europe and more precisely from Finland. The animations were created by using ArcGis program and Blender 3D graphics software. In ArcGis the GIS-database was modified for suitable format to be used in Blender. Based on the visual materials, objects were formed in Blender from polygons that reflect the geometry of the ice sheet and its environment. The movements and other events were modelled by animating them and their visual look was formed by assigning different materials for different objects. Lastly, the animation was post-processed through composite and then rendered out of the program in the desired format. The results of the study were two animations about the activities related to the continental ice sheet in Northern Europe and Finland. The animation of Northern Europe is a general overview of growth and retreat of the ice sheet between 34–10 ka. The main result of the study is an animation of retreat of the ice sheet during deglaciation in Finland between 14–10 ka. The animation of the Finnish area visualizes ice lobes and stagnant ice areas between them. In addition to the ice sheet the animation also visualizes ice lakes, terminal moraines and calving of the ice sheet, as well as the sub-aquatic and supra-aquatic regions in Finland. The study can be further refined by adding all existing research data of ice margin ...